Die Website als Instrument der Vertrauensbildung in der Urlaubshotellerie - Matthias Zeisberg (IU Internationale Hochschule, 2022)
– Trust is a very important factor in travel and tourism marketing. This also applies to first-time bookings in the holiday hotel industry, whose services with its many different facets can only be reliably assessed to a limited extent before the start of a trip. Against this background, this paper investigates the question which specific trust-promoting elements selected holiday hotels on the Baltic Sea coast of MecklenburgVorpommern use on their website. Of the eight elements examined, two are found to be more widespread: References to engagement in social media channels and the use of very different kinds of quality marks. Photos of employees, an illustrated description of the hotel's history and logos of partner companies can be found on about every fourth website. Customer reviews, press releases and the integration of an immediate rating option for website visitors bring up the rear of the ranking.
Keywords: M31; 650; tourism marketing; web design; trust elements